Reproduction of mothering in East Asia : a qualitative study of Japanese and South Korean mothers - Sidz, Malgorzata (My University, 2019)
The issues of motherhood and mothering remain one of the biggest factors influencing the gendered organisation of modern East Asian societies. Women are encouraged through different societal agents into becoming the main caregivers of children on the cost of their own careers and personal growth. The tendency is visible not only through women leaving work or changing to part-time occupations, but also through becoming the main decision-makers in children’s lives. This Master’s Thesis focuses on the data collected through extensive semi-structured interviews. Fourteen interviewees from South Korea and Japan reflect on the ways they were conditioned into making the choice of centering childcare in their lives. Based on the literature, the different factors are divided into the categories of biological, sociological and generational influence. The results of the study show a tendency towards the generational influence, as well as a “domino effect” of women following the decisions of their peers. Additional findings point at the changing trends regarding the sex preference for the baby, as well as diminishing role of the mother-in-law and the extended family in the East Asian society.
Keywords: Japan, South Korea, East Asia, gender studies, women, motherhood, mothering